From the Trenches - API Issues in Linked Geo Data - Robert H. Warren; David Evans (Linking Geospatial Data Workshop, 2014)

Sex, Privary and Ontologies - Adriel Dean-Hall; Robert H. Warren (Workshop on Search and Exploration of X-Rated Information (SEXI 2013), in proceedings of Sixth ACM International Conference on Web Search and Data Mining (WSDM 2013), 2013)

Creating specialized ontologies using Wikipedia: The Muninn Experience - Robert H. Warren (Proceedings of Wikipedia Academy: Research and Free Knowledge. (WPAC2012), 2012)
This paper reports on the experiences of the Muninn Project in creating specialized ontologies for historical governmental and military organizations using the Wikipedia data set and its Linked Open Data companion DBpedia. The motivation for the ontologies and the extraction methods used are explained and their pitfalls reviewed. Overall Wikipedia is a very accurate knowledge base from which multi-lingual concepts can be extracted. The caveat is that while the information is almost always present, it is not always straight-forward to retrieve because of missing structures or categorization information